Business Preservation of Batik Indonesia (Heritage), Challenges and The Solution - Dewi Kusumasari; Asri Noer Rahmi (Jurnal Ilmu Manajemen & Ekonomika, 2019)
This study aims to look at the effort to preserve Indonesian Batik which is one of the most valuable herit-ages that is owned by the Indonesian people, this research looks at what efforts can be done to keep the unique motifs and patterns in Indonesia and what obstacles are also faced solutions that can help preserve batik in Indonesia. The research method used in this study is qualitative, consisting of a literature review on Batik and Interview to several Batik industries in Jabodetabek and in Central Java, especially Solo and its surroundings. the process and the development of its coloring also held batik exhibitions for marketing and business development not only in Indonesia, but also to the Five Countries as a form of maintaining the work of creative industries in Indonesia.